دروس في الإنجليزية - بلقرمي سهام (جامعة محمد بوضياف المسيلة, 2024)
إنّ مطبوعة الدروس في اللغة الانجليزية التي وجِّهت لطلبة السنة أولى ماستر علم اجتماع التربية، جاءت وفق مقررات الوزارة التي تشجِّع على تعلّم وتوظيف والاستفادة من استخدام اللغة الإنجليزية في مختلف المجالات البحثية في العلوم الاجتماعية والإنسانية، فكان هذا العمل المُتّبِع للأدبيات النظرية في اللغة الإنجليزية ، وكذلك تخصص علم اجتماع التربية، محاولةً لاقتراح نموذج لتدريس المقياس ضمن هذا التخصص، يجمع بين استخدام مصطلحات التخصص والمساعدة على بناء تواصلٍ ضمن لغةٍ انجليزية تحمل صبغة علم اجتماع التربية انطلاقا من انتقاء بعض النصوص المختارة كنماذج، واقتراح بعض الأنشطة التدريبية التي تُعزِّز المكتسبات اللغوية في المجال. الكلمات المفتاحية: علم اجتماع التربية، فلسفة التربية، التعلّم، نصوص مختارة، الأنشطة التدريبية. Abstract : The publication of English Language Lessons, aimed at first-year students of the Master's Degree in Sociology of Education, has occurred in accordance with the decisions of the Ministry that encourage the learning, employment and benefit of the use of the English language in various research areas of the social sciences and humanities. This work; has followed the theoretical literature in the English language, as well as the specialty in sociology of education, with the aim of proposing a model for teaching this language of sociology of education. It combines the use of specialized terminology and helps in the construction of a communication within an English language that bears the character of sociology of education, based on the selection of some texts chosen as models;and on the proposal of some training activities that value linguistic acquisitions in the field. Keywords: sociology of education, philosophy of education, learning, selected texts, training activities